Uncoupling Protein 2 and Peroxisome Proliferator-Activated Receptor γ Gene Polymorphisms in Association with Diabetes Susceptibility in Chinese Han Population with Variant Glucose Tolerance. (5th April 2018) - Zhou, Meicen; He, Shuli; Ping, Fan; Li, Wei; Zhu, Lixin; Cui, Xiangli; Feng, Linbo; Zhao, Xuefeng; Zhang, Huabing; Li, Yuxiu; Sun, Qi
Abstract : Objective . To investigate the association of polymorphisms in uncoupling protein 2 (UCP2) and peroxisome proliferator-activated receptor (PPAR γ ) with glucolipid metabolism in Chinese Han population. Methods . Five hundred eighty-nine subjects were divided into normal glucose tolerance (NGT) group (n = 198 ) and abnormal glucose tolerance group (n = 358 ). HbA1c, blood lipid profile, plasma glucose, and insulin were determined. Insulin sensitivity (HOMA-IR and Matsuda index (ISIM )) and insulin secretion indexes (HOMA- β, early and total phase disposition index) were evaluated. Eight potential functional SNPs in UCP2 and 7 in PPAR γ were selected. SNPs were genotyped on Sequenom MassARRAY platform. Results . The GG genotype of rs2920502 in PPAR γ was associated with decreased risk of impaired glucose tolerance (G allele: OR: 0.818, 95%CI: 0.526–0.969, P = 0.042 ; GG: OR: 0.715, 95%CI: 0.527–0.97, P = 0.031 ). The TT genotype of rs3856806 in PPAR γ was associated with increased risk of impaired glucose tolerance (T allele: OR: 1.46, 95%CI: 1.055–2.017, P = 0.022 ; TT: OR: 1.58, 95%CI: 1.104–2.761, P = 0.032 ). The GG genotype of rs2920502 in PPAR γ had better blood glucose and increased insulin secretion and had lower HOMA-IR than GC/CC genotypes. Conclusion . It probably could prevent insulin resistance in early stage by classifying the genotype of rs649446 and rs7109266 in UCP2. The GG genotype of rs2920502 in PPAR γ had a decreased risk for diabetes. The TT genotype of rs3856806 in PPAR γ had an increased risk for diabetes.